2017
DOI: 10.2196/jmir.6524
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone-Delivered Cognitive Behavioral Therapy for Insomnia: A Randomized Waitlist Controlled Trial

Abstract: BackgroundThis study is one of the first randomized controlled trials investigating cognitive behavioral therapy for insomnia (CBT-I) delivered by a fully automated mobile phone app. Such an app can potentially increase the accessibility of insomnia treatment for the 10% of people who have insomnia.ObjectiveThe objective of our study was to investigate the efficacy of CBT-I delivered via the Sleepcare mobile phone app, compared with a waitlist control group, in a randomized controlled trial.MethodsWe recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 51 publications
10
127
2
2
Order By: Relevance
“…For clinical populations, two studies Computer-aided training on how to use the apps; participants were also allocated a coach to help with app usage HADS recruited people with major depression 36,43 , two individuals with bipolar disorder 28,30 , one young people in primary care with any mental health condition 40 . Others recruited individuals from the general population with self-reported mild-to-moderate depression 26,27,39,41 , suicidal thoughts/tendencies 42 , probable attention-deficit/hyperactivity disorder (ADHD) 37 , anxiety disorders 29,33 , insomnia 31 , or symptoms of post-traumatic stress disorder (PTSD) 35 . One further study examined older adults with memory complaints 38 .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For clinical populations, two studies Computer-aided training on how to use the apps; participants were also allocated a coach to help with app usage HADS recruited people with major depression 36,43 , two individuals with bipolar disorder 28,30 , one young people in primary care with any mental health condition 40 . Others recruited individuals from the general population with self-reported mild-to-moderate depression 26,27,39,41 , suicidal thoughts/tendencies 42 , probable attention-deficit/hyperactivity disorder (ADHD) 37 , anxiety disorders 29,33 , insomnia 31 , or symptoms of post-traumatic stress disorder (PTSD) 35 . One further study examined older adults with memory complaints 38 .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Depressive symptoms were measured as a primary outcome in 12 studies, and as a secondary outcome in six. The following tools were used: the Depression Anxiety Stress Scale 44 depression subscale in three studies 29,39,40 ; the Center for Epidemiological Studies Depression scale 45 in four 31,32,38,41 ; the Beck Depression Inventory II 46 in three 34,36,43 ; the Patient Health Questionnaire 47 in six 26,27,33,35,42,43 ; the Hamilton Rating Scale for Depression 48 in one 30 ; the Hospital Anxiety Depression Scale 49 in one 37 ; and the Montgomery-Å sberg Depression Rating Scale 50 in one 28 .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…19 The low remission rate associated with CBTI without psychological support may be associated with its use in patients with more severe chronic insomnia disorder. These individuals are likely to require more intensive support from higher levels in the pyramid, such as 20,21 However, despite being highly effective, the second limitation of fully automated CBTI studies is the dropout rate, which has been reported as 39% to 45%, higher than that of face-to-face CBTI. 20,21 Therefore, the number of sessions that patients complete could be a crucial factor for the success of fully automated CBTI as an intervention.…”
Section: Introductionmentioning
confidence: 99%
“…For an extended overview of the setup, the statistical analysis and the results of the RCT, we refer to [22]. In the RCT, 74 participants were allocated as an active treatment group to the SleepCare system and 77 participants to a waiting list group that received intervention after the active group.…”
Section: Results From the Rctmentioning
confidence: 99%
“…To evaluate the acceptability of the system and the therapy process in real-life situations, we now turn to the testing and user evaluation phases. We distinguished four phases of testing and evaluation: (a) automated testing for error code [19]; (b) expert analysis; (c) user evaluation; and, finally, (d) a randomized controlled trial (RCT) with insomnia patients [22]. Below, we will summarize the methodology and some interesting findings.…”
Section: Testing and User Evaluationmentioning
confidence: 99%